Sperm kinematics and morphometric subpopulations analysis with CASA systems: a review - Valverde Abarca, Anthony; Castro-Morales, Olivier; Mdrigal-Valverde, Mónica (Revista de Biología Tropical, 2019)
Sperm kinematics and morphometric subpopulations analysis with CASA systems: a review. The subjective evaluation of seminal quality has given way to the use of objective assessment techniques by CASA technology (computer-assisted semen analysis). The application of principal components (PC) and clustering methods to reveal subpopulations of spermatozoa is a powerful tool to evaluate raw semen and processed cell suspensions, but not many researchers are aware of the technique. PC analysis is a multivariate statistical method that reduces the number of variables used in subsequent calculations used to describe the data. By integrating the original variables according to their coherence in a database into a new complex mathematical variable, clearly defined homogenous subpopulations of spermatozoa can be defined. Kinematic, morphometric, morphological or DNA integrity tests may apply to characterize it and understand the reproductive biology of the spermatozoon. In recent years there has been a substantive change in the conceptual paradigm regarding what an ejaculate is. It should be said that until recently it was considered that the representative population (billions) of sperm was made up of "equivalent" cells with a common goal: to be the one that could finally fertilize the oocyte. The verification that the set of spermatozoa is grouped in distinct subpopulations, according to their kinematic and morphometric characteristics, opens the way towards a more cooperative vision. Besides, we have seen that the subpopulation distribution is different among males, which seems to indicate different strategies that can be understood within another paradigm, that of sperm competition between different ejaculates. The existence of heterogeneous subpopulations of spermatozoa in the ejaculate that show kinematics and morphometric patterns is widely known but the biological meaning of these different sperm subpopulations is still not clear. Although the role of the different subpopulations remains unknown, the work should continue in that direction.